2014
DOI: 10.1007/s13404-014-0140-2
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagram of Au-Al-Cu at 500 °C

Abstract: Diffusion couples and equilibrated alloys were used to construct the isothermal phase diagram of Au-Al-Cu at 500°C. Electron microprobe analyses were performed to determine the phase compositions and phase relationships. Two ternary phases and 10 three-phase equilibriums were determined in this study. Four additional three-phase equilibriums were estimated to meet the criteria for phase relationships. The δ (Au 2 Al) phase exhibited a wide range of solubility, and the lattice parameters were examined by X-ray.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…These authors also gave a vertical cross section of this system with 76 wt % Au and determined the relationships between the existing phases. 15 The latest version of the isothermal cross section at 500 °C was by Li et al 16 Based on the constructed isothermal cross section, they determined the existence of 2 three-component phases (ε and β) as well as 10 phase equilibria established between three phases: Al-AuAl 2 -Al 2 Cu, A1 2 Cu-ε-AlCu, AuAl 2ε-AlCu, AuAl 2 -AuAl-γ, AuAl-δ(Au 2 Al)-γ, δ(Au 2 Al)-α-β, Au 8 Al 3δ(Au 2 Al)-Au 4 Al, AlCu-AuAl 2 -Al 9 Cu 11 , Al 9 Cu 11 -AuAl 2 -Al 2 Cu 3 , and Al 2 Cu 3 -AuAl 2 -γ. The presence of four three-phase regions was also determined: β-δ(Au 2 Al)-γ, α-β-γ, α-δ(Au 2 Al)-Au 4 Al, and AuAl 2 -ε-Al 2 Cu.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors also gave a vertical cross section of this system with 76 wt % Au and determined the relationships between the existing phases. 15 The latest version of the isothermal cross section at 500 °C was by Li et al 16 Based on the constructed isothermal cross section, they determined the existence of 2 three-component phases (ε and β) as well as 10 phase equilibria established between three phases: Al-AuAl 2 -Al 2 Cu, A1 2 Cu-ε-AlCu, AuAl 2ε-AlCu, AuAl 2 -AuAl-γ, AuAl-δ(Au 2 Al)-γ, δ(Au 2 Al)-α-β, Au 8 Al 3δ(Au 2 Al)-Au 4 Al, AlCu-AuAl 2 -Al 9 Cu 11 , Al 9 Cu 11 -AuAl 2 -Al 2 Cu 3 , and Al 2 Cu 3 -AuAl 2 -γ. The presence of four three-phase regions was also determined: β-δ(Au 2 Al)-γ, α-β-γ, α-δ(Au 2 Al)-Au 4 Al, and AuAl 2 -ε-Al 2 Cu.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of four three-phase regions was also determined: β-δ(Au 2 Al)-γ, α-β-γ, α-δ(Au 2 Al)-Au 4 Al, and AuAl 2 -ε-Al 2 Cu. 16 Bhatia et al, 17,18 who investigated the phase compositions in alloys of the Cu−Al−Au system that characterized the shape memory effect, made an isothermal cross section of this system at 750 °C. They confirmed that the βand γ-phases penetrate deep into the ternary of the phase diagram at 750 °C.…”
Section: Introductionmentioning
confidence: 99%